2007
DOI: 10.1002/jemt.20502
|View full text |Cite
|
Sign up to set email alerts
|

Bioimaging TOF‐SIMS: High resolution 3D imaging of single cells

Abstract: The distribution of phosphocholine ions (m/z 184, m/z 86), sodium ions, and potassium ions in thyroid tumor cells was analyzed by imaging TOF-SIMS. Repeated sputtering with a C(60) (+) source and subsequent analysis with a Bi(3) (+) gun produced a series of 138 images that were stacked to make a 3D display of the chemistry of cells. Phosphocholine was seen in the plasma membrane (m/z 184) and intracellular membranes (m/z 86). The different fragmentation of the phospholipid probably reflects the chemical compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 21 publications
2
84
0
3
Order By: Relevance
“…[19][20][21][22] Typically, Bi cluster ToF-SIMS equipped with a liquid metal ion gun (LMIG) has been used for image analysis because the ionized Bi n q + clusters (n = 1-7, q = 1, 2) achieve high brightness. 23,24) Also, it was reported that Bi monomer ions were the optimum primary ion species for analyzing hydrogen and deuterium in materials. 25,26) Concerning steels samples, dynamic SIMS has been shown to be an effective method for detecting deuterium or hydrogen in different steels.…”
Section: Micro-portion Image Analysis Of Light Elements In Fe-cr Basementioning
confidence: 99%
“…[19][20][21][22] Typically, Bi cluster ToF-SIMS equipped with a liquid metal ion gun (LMIG) has been used for image analysis because the ionized Bi n q + clusters (n = 1-7, q = 1, 2) achieve high brightness. 23,24) Also, it was reported that Bi monomer ions were the optimum primary ion species for analyzing hydrogen and deuterium in materials. 25,26) Concerning steels samples, dynamic SIMS has been shown to be an effective method for detecting deuterium or hydrogen in different steels.…”
Section: Micro-portion Image Analysis Of Light Elements In Fe-cr Basementioning
confidence: 99%
“…Indeed, this study, along with the previous one, shows that the chemical composition of animal cells can be reconstructed in three dimensions by ToF-SIMS imaging in combination with repeated sputter cycles that erode the sample in a layer-by-layer fashion and thereby make the inner structure of the cells accessible for SIMS analysis. A similar study using C 60 for sputtering and Bi þ 3 for analysis has been reported on freeze-fractured, freeze-dried thyroid tumor cells in which it is claimed that internal cell compartments were imaged (Nygren et al, 2007). However, in this case the authors could only detect and image, sodium, potassium, m/z 86, which is not identified, but could be a fragment of leucine/isoleucine or choline, and m/z 184 from phosphocholine.…”
Section: Normal Rat Kidney Cellsmentioning
confidence: 69%
“…Mass spectrometric imaging is capable of detecting lipid species in intact biological cells and tissue, and providing lateral resolution down to the micron scale (13)(14)(15) ) and recording the ejected secondary ions as a function of their m/z and point of origin on the sample to form a "chemical map". The introduction of polyatomic primary ion beams such as C 60 + has facilitated the analysis of molecular species beyond the sample surface allowing complex chemical distributions to be studied in both two and three dimensions ( 14,17 ).…”
Section: Sampling the X Laevis Embryosmentioning
confidence: 99%